Rethinking literacy instruction for nonspeaking autistic learners: a perspective on evidence, exclusion, and the right to read - Kimhi, Yael (Frontiers in Education, 2025)
As inclusive policies expand, more and more children with high support needs, including those with autism spectrum disorder (ASD), are placed in general education classrooms. However, nonspeaking autistic learners are among the most systematically excluded learners from equitable literacy education. Despite growing international commitments to educational equity, these learners, who represent a unique subgroup within the autism spectrum, continue to face barriers due to a lack of teacher preparedness, outdated assumptions about language prerequisites for reading, and insufficient focused research. This Perspective article argues that the exclusion of nonspeaking learners from literacy instruction reflects a gap in instructional vision and preparedness. Drawing on recent research, clinical insights, and practice-based knowledge, we highlight the barriers that limit access to literacy for this population, synthesize evidence-based approaches, and conclude by calling for a shift in educational discourse, from questioning whether nonspeaking autistic children can learn to read to ensuring that they are given meaningful opportunities to do so. Literacy is not merely an academic goal; it is a fundamental right that must be upheld for all students, regardless of their mode of communication.